Pengaruh Kenaikan Suhu Cairan Developer Terhadap Densitas Radiograf - Septiadi, Jujun; Anam, Choirul; Azam, Much (BERKALA FISIKA, 2008)
This aim of the research is to obtain an optimal developer temperature. The increase of dilution temperature of developer to radiograph density has been measured. The Research is conducted with measuring radiograph density with a certain exposure factor and materials and varies temperature among 170 C – 320 C.  The result indicates that the higher of temperature is the greater of its density value. The optimal temperature obtained at spanning temperature among 200 C – 230 C.   Key words: The dilution temperature of developer, density of radiograph, optimal temperature